Adjusting Aspergillus niger pellet diameter, population heterogeneity, and core architecture during shake flask cultivation - K. Engelbert; C. Deffur; T. C. Cairns; F. Zhang; T. Kheirkhah; H. Winter; S. Junne; P. Neubauer; H. Briesen; V. Meyer (Biotechnology for Biofuels and Bioproducts)
Abstract Background Filamentous fungi form a range of macromorphologies during submerged cultivation including dispersed mycelia, loose clumps, and pellets. Macromorphological development is usually heterogenous, whereby mixtures form due to a complex interplay of growth, aggregation, and fragmentation. Submerged macromorphology strongly impacts product titres and rheological performance. Nevertheless, studies that systematically investigate the quantitative effect of cultivation parameters on macromorphology and heterogeneity are lacking. Results In this study, we have developed shake flask cultivation conditions which enable reproducible macromorphological control of the multipurpose cell factory Aspergillus niger. Tested culture parameters included various spore titres, concentration of talc microparticles, shaking frequency, and presence/absence of baffles (n = 48 conditions). We quantified macromorphology (e.g., pellet diameter) using high-throughput two-dimensional image analysis and report intra-flask heterogeneity and flask-to-flask variation. These data identified optimal culture conditions which cause minimal macromorphological variation within individual flasks and between technical replicates. We demonstrate that pellet diameter can be reproducibly adjusted between experiments using simple cultivation conditions, and use these parameters to prove larger pellets secrete more protein while consuming less glucose. Linear regression models allowed us to identify spore concentration, shaking frequency, and talc concentration as crucial parameters impacting pellet diameter. Finally, we used a newly developed microtomography (µ-CT) approach to quantify the three-dimensional internal architecture for thousands of pellets at the cellular level. Cultivation conditions drastically impacted internal architecture. For the first time we report distinct types of pellets- those formed from a single (I) or multi-spore (II) core, and additionally pellets formed by agglomeration of mature pellets (III). Remarkably, these data show that a pellet of 2 mm consists of up to about 30 m of total hyphal length and contain approximately 200,000 tips. Conclusions This study identifies simple methods for adjusting macromorphology and heterogeneity, which will enable facile testing of different macromorphologies for maximizing product titres. For the first time we have investigated how pellet internal architecture is impacted by numerous culture parameters. We propose a new pellet classification system based on internal spore core architecture, thus broadening our understanding of fungal macromorphological development and opening up new avenues for bioprocess or strain engineering.